Trim the sail: A rare cause of newborn hypoxia - Khalid A. Katranji; Max Jacob Spiro; Cecilia A. Albaro; Harma K. Turbendian; Gretchen L. Kopec (Annals of Pediatric Cardiology)
The right venous valve is critical to the proper development of the fetal heart. As the right venous valve degenerates later in fetal development, residual structures can remain, such as the terminal crest, Eustachian valve, Thebesian valve, and a prominent Chiari network, with a sail-like appearance resembling a spinnaker. While these structures are often incidentally found on adult echocardiograms, we present a case of a term neonate with hypoxia secondary to a persistent right valve of the sinus venosus.